Designing an interactive multimedia instructional environment: The Civil War Interactive - Cates , Ward M.; Fontana , Lynn A.; White , Charles S. (Research in Learning Technology)
This article describes the rationales behind the design decisions made in creating The Civil War Interactive, an interactive multimedia instructional product based on Ken Burns’’s film series The Civil War. DOI:10.1080/0968776930010202